2017
DOI: 10.3390/ijms18040787
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Diet Interaction and Precision Nutrition in Obesity

Abstract: The rapid rise of obesity during the past decades has coincided with a profound shift of our living environment, including unhealthy dietary patterns, a sedentary lifestyle, and physical inactivity. Genetic predisposition to obesity may have interacted with such an obesogenic environment in determining the obesity epidemic. Growing studies have found that changes in adiposity and metabolic response to low-calorie weight loss diets might be modified by genetic variants related to obesity, metabolic status and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
103
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 134 publications
(197 reference statements)
0
103
0
11
Order By: Relevance
“…While a number of interventions have been studied, a considerable amount of variability has been reported in weight and/or fat loss among individuals, even when participating in the same intervention . One factor that has been suggested to influence an individual's response to a weight management intervention is genetics . For example, findings from the Genome Wide Association Studies have identified genetic polymorphisms associated with obesity and aspects related to obesity, such as energy expenditure, appetite control and lipid metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…While a number of interventions have been studied, a considerable amount of variability has been reported in weight and/or fat loss among individuals, even when participating in the same intervention . One factor that has been suggested to influence an individual's response to a weight management intervention is genetics . For example, findings from the Genome Wide Association Studies have identified genetic polymorphisms associated with obesity and aspects related to obesity, such as energy expenditure, appetite control and lipid metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been suggested that such efforts may not be needed, and that the use of biochemical and/or anthropometric indices may be enough in formulating personalised dietary interventions, as these are environmental risk factors known to influence disease risknamely CVD risk (70) . To that, we respond that investigating gene-nutrient interactions should remain a priority for the refinement of dietary interventions and the management of disease risk, as robust evidence now suggests that genetic variants (1) are able to modify the response to interventions (71) , and (2) can trigger adverse health outcomes when exposed to high-risk environmental factors (71) , a concept we term 'context-dependency of molecular behaviour'. Additionally, several studies have shown that gene polymorphisms respond to nutrient interaction, affecting biochemical markers of metabolic and CVD (72)(73)(74) and obesity (71) .…”
Section: Context-dependency Of Molecular Behaviourmentioning
confidence: 99%
“…To that, we respond that investigating gene-nutrient interactions should remain a priority for the refinement of dietary interventions and the management of disease risk, as robust evidence now suggests that genetic variants (1) are able to modify the response to interventions (71) , and (2) can trigger adverse health outcomes when exposed to high-risk environmental factors (71) , a concept we term 'context-dependency of molecular behaviour'. Additionally, several studies have shown that gene polymorphisms respond to nutrient interaction, affecting biochemical markers of metabolic and CVD (72)(73)(74) and obesity (71) . However, how these polymorphisms interact with nutrients in different contexts of health, disease, drug interventions and across ethnicities has not been investigated to date, and is needed for consideration in future research.…”
Section: Context-dependency Of Molecular Behaviourmentioning
confidence: 99%
“…Indeed, studies on humans (e.g., Tanaka 2014), rats (e.g., Liu and Lloyd 2013), mice (e.g., Smith et al 2000), fruit flies (Reddiex et al 2013), and field crickets (Rapkin et al 2017) all indicate that the intake of macronutrients has a genetic basis. The predisposition to the deleterious effects of dietary overconsumption also appears to have a genetic basis that varies with the nutritional environment (van der Klaauw and Farooqi 2015), with genotype-by-diet interactions for weight gain and obesity being demonstrated in mice (Sutton et al 2006;Gordon et al 2008), D. melanogaster (Reed et al 2010), and humans (Qi and Cho 2008;Heianza and Qi 2017). While there is less support, there is some evidence in humans to suggest that the genes for dietary intake are linked to those for obesity (e.g., Faith et al 1999;Hasselbalch et al 2010).…”
Section: Introductionmentioning
confidence: 99%